Nature-based solutions (NbS) for reducing the risk of shallow landslides: Where do we stand?. (December 2019) - de Jesús Arce-Mojica, Teresa; Nehren, Udo; Sudmeier-Rieux, Karen; Miranda, Patricia Julio; Anhuf, Dieter
Abstract: Nature-based solutions (NbS) are highlighted in international agreements such as the Sendai Framework for Disaster Risk Reduction 2015–2030 as promising strategies to reduce disaster risk, adapt to climatic change, and strengthen community resilience. Particular focus is placed on the role of vegetation to prevent or mitigate the impacts of natural hazards and climatic extreme events. Protection forests that aim to minimize the risk of shallow landslides and other slope processes are among the numerous examples of how vegetation can reduce disaster risk and support communities to cope with natural hazards. However, there is no existing systematic review of the protection functions that vegetation offers in different mountain environments and many studies only focus on one specific controlling factor - such as the root systems - without considering NbS as an integrated concept. We performed a detailed investigation into shallow landslides as the most frequent slope processes, and conducted a systematic literature review based on two peer-reviewed bibliographic databases, Scopus and Science Direct, to ascertain the extent to which vegetation is identified as a controlling factor and the targeting of NbS for risk reduction. We assessed more than 13, 000 articles published from 2000 to 2018 and conducted an in-depth evaluation of the 275 articles that satisfied the assessment criteria. Our results show that despite the promotion of NbS in internal policies, little research has been published on this topic; however, this has increased over the last decade. We therefore encourage transdisciplinary studies that integrate NbS for shallow landslides reduction. Highlights: Existing research mainly focuses on slope stability and vegetation aspects. Most research is conducted in China, USA and Europe. Several variants of similar terms are used to address Nature-based Solutions. Current research often discusses Nature-based Solutions at a descriptive and conceptual level.